Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,
x.2/7.3/4=5/21
x.3/14=5/21
x=5/21:3/14
x=10/9
b,
x.1/2=1/3
x=1/3:1/2
x=2/3
c,
x:4/5=25/8:5/4
x:4/5=5/2
x=5/2.4/5=2
A, x= 5/25 : 3/4 : 2/7 = 14/15
B, x=1/3 : 1/2 = 2/3
C, x=(25/8 : 5/4)x4/5 = 5/2 x 4/5 = 2
a)
\(x.\frac{7}{9}=\frac{2}{3}+2\frac{1}{2}\)
\(x.\frac{7}{9}=\frac{19}{6}\)
\(x=\frac{19}{6}:\frac{7}{9}\)
\(x=\frac{57}{14}\)
b) \(\frac{5}{7}+x:\frac{9}{4}=\frac{4}{3}\)
\(x:\frac{9}{4}=\frac{4}{3}-\frac{5}{7}\)
\(x:\frac{9}{4}=\frac{13}{21}\)
\(x=\frac{13}{21}.\frac{9}{4}\)
\(x=\frac{39}{28}\)
Câu b:
\(\frac{21}{8}:\frac{5}{6}+\frac{1}{2}:\frac{5}{6}\)
= \(\frac{63}{20}+\frac{3}{5}\)
= \(\frac{15}{4}\)
\(\left(\frac{21}{8}+\frac{1}{2}\right):\frac{5}{6}\)
\(\frac{25}{8}:\frac{5}{6}\)
\(\frac{25}{8}.\frac{6}{5}\)
\(\frac{30}{8}\)
\(\frac{4}{3}+x.\frac{2}{3}-\frac{1}{4}=\frac{53}{12}\)
\(x.\frac{2}{3}-\frac{1}{4}=\frac{53}{12}-\frac{4}{3}\)
\(x.\frac{2}{3}-\frac{1}{4}=\frac{37}{12}\)
\(x.\frac{2}{3}=\frac{37}{12}+\frac{1}{4}\)
\(x.\frac{2}{3}=\frac{10}{3}\)
\(x=\frac{10}{3}:\frac{2}{3}\)
\(x=\frac{30}{6}=5\)
Vậy x = 5
mik ko chắc
\(\frac{4}{3}+x.\frac{2}{3}-\frac{1}{4}=4\frac{5}{12}\)
\(\frac{4}{3}+x.\frac{2}{3}=4\frac{5}{12}+\frac{1}{4}\)
\(\frac{4}{3}+x.\frac{2}{3}=\frac{53}{12}+\frac{1}{4}\)
\(\frac{4}{3}+x.\frac{2}{3}=\frac{14}{3}\)
\(x.\frac{2}{3}=\frac{14}{3}-\frac{4}{3}\)
\(x.\frac{2}{3}=\frac{10}{3}\)
\(x=\frac{10}{3}:\frac{2}{3}\)
\(x=5\)
\(x\cdot\frac{1}{3}+x\cdot\frac{2}{5}-4=3\)
\(x\cdot\left(\frac{1}{3}+\frac{2}{5}\right)-4=3\)
\(x\cdot\frac{11}{15}=7\)
\(x=\frac{105}{11}\)
\(x.\frac{1}{3}+x.\frac{2}{5}-4=3\)
\(\Rightarrow x.\left(\frac{1}{3}+\frac{2}{5}\right)=7\)
\(\Rightarrow x.\left(\frac{5}{15}+\frac{6}{15}\right)=7\)
\(\Rightarrow x.\frac{11}{15}=7\Rightarrow x=7:\frac{11}{15}=\frac{105}{11}\)
Vậy x = 105/11
1-\(\left(3\frac{3}{8}+x-2\frac{5}{24}\right)\)\(.\frac{12}{17}=0\)
\(\Rightarrow\left(3\frac{3}{8}+x-2\frac{5}{24}\right)\)\(.\frac{12}{17}\)\(=1\)
\(\frac{27}{8}+x-\frac{53}{24}\) \(=1:\frac{12}{17}\)
\(\frac{27}{8}+x=\frac{17}{12}+\frac{53}{24}\)
\(\frac{27}{8}+x=\frac{34+53}{24}\)
\(\frac{27}{8}+x=\frac{87}{24}\)
\(x=\frac{87}{24}-\frac{27}{8}\)
\(x=\frac{87-81}{24}\)
\(x=\frac{6}{24}=\frac{1}{4}\)
\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}+\frac{1}{3}\right)=\frac{4}{5}.\frac{3}{3}=\frac{4}{5}.1=\frac{4}{5}\)
\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}+\frac{1}{6}\right)=\frac{3}{4}:\frac{2}{3}=\frac{9}{8}\)
\(\frac{2}{3}.\frac{4}{5}-\frac{1}{3}.\frac{4}{5}=\frac{4}{5}\left(\frac{2}{3}-\frac{1}{3}\right)=\frac{4}{5}.\frac{1}{3}=\frac{4}{15}\)
\(\frac{1}{2}:\frac{3}{4}-\frac{1}{6}:\frac{3}{4}=\frac{3}{4}:\left(\frac{1}{2}-\frac{1}{6}\right)=\frac{3}{4}:\frac{1}{3}=\frac{9}{4}\)
\(\frac{2}{3}.\frac{4}{5}+\frac{1}{3}.\frac{4}{5}=\left(\frac{2}{3}+\frac{1}{3}\right).\frac{4}{5}=1.\frac{4}{5}=\frac{4}{5}\)
\(\frac{1}{2}:\frac{3}{4}+\frac{1}{6}:\frac{3}{4}=\frac{1}{2}.\frac{4}{3}+\frac{1}{6}.\frac{4}{3}=\left(\frac{1}{2}+\frac{1}{6}\right).\frac{4}{3}=\frac{2}{3}.\frac{4}{3}=\frac{8}{9}\)
c,d tương tự
Tìm x biết:
a) (15 × 19 – x – 0,15):0,25 = 15 : 0,25
b)\(2\frac{2}{3}-x=\frac{1}{3}\cdot\frac{6}{2}\)
a) (15 x 19 - x - 0,15) : 0,25 = 15 : 0,15
(285 - x - 0,15) : 0,25 = 60
(285 - x - 0,25) = 60 : 0,25
( 285 - x - 0,25) = 15
285 - x = 15 + 0,25
285 - x = 15,25
x = 285 - 15,25
x = 269,75
a ) \(x+x\times\frac{1}{3}\div\frac{2}{9}+x\div\frac{2}{7}=252\)
\(x\times1+x\times\frac{1}{3}\div\frac{2}{9}+x\div\frac{2}{7}=252\)
\(x\times1+x\times\frac{1}{3}\times\frac{9}{2}+x\times\frac{7}{2}=252\)
\(x\times1+x\times\frac{9}{6}+x\times\frac{7}{2}=252\)
\(x\times\left(1+\frac{9}{6}+\frac{7}{2}\right)=252\)
\(x\times6=252\)
\(x=252\div6\)
\(x=42\)
b ) \(\left(3\times x-0,8\right)\div x+14,5=15\)
\(\left(3\times x-0,8\right)\div x=15-14,5\)
\(\left(3\times x-0,8\right)\div x=0,5\)
\(0,8\div x=3-0,5\)
\(0,8\div x=2,5\)
\(x=0,8\div2,5\)
\(x=0,32\)
\(\frac{2}{3}x+\frac{3}{4}=3\)
\(\frac{2}{3}x=3-\frac{3}{4}=\frac{9}{4}\)
\(x=\frac{9}{4}:\frac{2}{3}\)
\(x=\frac{27}{8}\)
2/3 . x + 3/4 = 3
2/3 . x = 3 - 3/4
2/3 . x =9/4
x = 9/4 : 2/3
x =27/8